Interlaboratory assays from the fungal PCR Initiative and the Modimucor Study Group to improve qPCR detection of Mucorales DNA in serum: one more step toward standardization - Rocchi, Steffi; Scherer, Emeline; White, P Lewis; Guitton, Audrey; Alanio, Alexandre; Botterel, Françoise; Bougnoux, Marie Elisabeth; Buitrago, Maria José; Cogliati, Massimo; Cornu, Marjorie; Damiani, Celine; Denis, Julie; et al. (Journal of clinical microbiology, 2025)
UNLABELLED: The aim of this study was to identify parameters influencing DNA extraction and PCR amplification efficiencies in an attempt to standardize Mucorales qPCR. The Fungal PCR Initiative Mucorales Laboratory Working Group distributed two panels of simulated samples to 26 laboratories: Panel A (six sera spiked with Mucorales DNA and one negative control serum) and Panel B (six Mucorales DNA extracts). Panel A underwent DNA extraction in each laboratory according to the local procedure and were sent to a central laboratory for testing using three different qPCR techniques: one in-house qPCR assay and two commercial assays (MucorGenius and Fungiplex). Panel B DNA extracts were PCR amplified in each laboratory using local procedures: nine in-house qPCR assays and two commercial kits (MucorGenius and MycoGENIE). All data were compiled and anonymously analyzed at the central laboratory. For Panel A, a total of six different automated platforms and five manual extraction methods were used. Positive rates were 64%, 70%, and 89%, for the MucorGenius, Fungiplex, and the in-house qPCR assay, respectively. Using a large volume of serum for DNA extraction provided the highest analytical sensitivity (82.5% for 1 mL compared with 62.7% for smaller volumes, P < 0.01). For Panel B, five in-house qPCR assays and two commercial kits had >78% positivity. Using larger PCR input volumes (≥7 μL) was associated with the highest sensitivity at 95.5% compared to 58.3% when lower input volumes were used (P < 0.01). Using larger sample volumes for nucleic acid extraction and DNA template volumes for PCR amplification significantly improves the performance of Mucorales qPCR when testing serum. IMPORTANCE: Mucormycosis is a life-threatening mold infection affecting immunosuppressed patients but also other patients with diabetes or trauma. Better survival is linked to shorter delays in diagnosis and treatment initiation. Detection of Mucorales-free DNA in serum or plasma using quantitative PCR allows a prompt diagnosis and earlier treatment. Several techniques and protocols of quantitative Mucorales PCR are used in Europe, and improving performance remains a common objective of laboratories participating in the fungal PCR Initiative Working Group. This study, which combined results from 26 laboratories in Europe, showed that the main parameters underpinning sensitivity are the preanalytical variables (volume of serum used for DNA extraction and DNA template volume), irrespective of the extraction platforms and qPCR assay/platform.
Keywords: DNA fungální; Real-Time Polymerase Chain Reaction; lidé; Molecular Diagnostic Techniques; DNA, Fungal; Mucormycosis; diagnostické techniky molekulární; mukormykóza; Sensitivity and Specificity; kvantitativní polymerázová řetězová reakce; senzitivita a specificita; Mucorales; Humans